Dogmatic Questions and Practical Issues in the Unnoficial Bilateral Theological Dialogue between the Eastern Orthodox Churches and the Oriental Orthodox Churches - Florescu, Marius (Review of ecumenical studies, 2019)
In the following study we will try to identify some dogmatic aspects and practical issues which have resulted from the dialogue between the Eastern Orthodox Churches and the Oriental Orthodox Churches, that occurred between the 1960's and the 1980's, just in the beginning of the theological dialogue, in the so-called unofficial dialogue. We will mainly underline the non-theological factors that shaped the bilateral relations between these Christians over the centuries and when the dialogue was initiated.